Linking PFAS partitioning behavior in sewage solids to the solid characteristics, solution chemistry, and treatment processes. (May 2021) - Ebrahimi, Farshad; Lewis, Asa J.; Sales, Christopher M.; Suri, Rominder; McKenzie, Erica R.
Abstract: Per- and polyfluoroalkyl substances (PFAS) have gained increasing attention due to the potential health risks that they present. Secondary sludge and biosolids are known as notable PFAS emission routes to the environment. In this study, partitioning behavior of 14 PFAS were investigated across four secondary wastewater treatment types (activated sludge, trickling filter, biological nutrient removal, and rotating biological contactor; n = 10) and three sludge stabilization methods (composting, aerobic digestion, and anaerobic digestion; n = 6). Batch experiments were conducted to evaluate how PFAS sorption to secondary sludge and biosolid was affected by various treatment methods, solid properties, and solution chemistry parameters. Insignificant differences in compound-specific partitioning coefficients ( K d ) were observed among the four secondary treatment methods. However, sludge stabilization resulted in significantly different partitioning behavior among biosolid samples, in which anaerobically digested biosolids generally had significantly higher K d values compared to aerobically digested and composted biosolids (anaerobic digestion > aerobic digestion > composting). Multiple linear regression models were developed to explain analyte-specific Kd values across the biosolid samples and identified that solid-specific property significance was as follows: protein fraction > organic matter fraction > lipid fraction. Stabilization generally decreased the PFAS sorption capacity relative to the secondary sludge samples. Furthermore, PFAS K d increased with elevated calcium concentrations and ionic strengths and decreased with increasing pH values in sludge and biosolid samples. These findings could inform the decision-making process to reduce the release of PFAS to the environment. Highlights: Sludge stabilization significantly affected PFAS Kd in biosolid. Secondary treatment did not significantly affect PFAS Kd in sludge. Biosolids generally had significantly lower PFAS Kd compared to secondary sludge. Protein was stronger predictor of PFAS Kd than organic matter or lipid fraction. Elevated mono- and divalent cations increased PFAS Kd, while high pH decreased it.